Subcutaneous application of levothyroxine as successful treatment option in a patient with malabsorption - Gröner, Jan; Lehnhoff, Daniel; Piel, David; Nawroth, Peter Paul; Schanz, Jurik; Rudofsky, Gottfried (The American journal of case reports, 2013)
Background: Hypothyroidism can usually be treated effectively by oral levothyroxine supplementation. There are, however, some rare circumstances, when oral levothyroxine application is not sufficient, for example malabsorption, interactions with food or other medications, or various gastrointestinal diseases. - Case Report: We present a 42 year old woman with refractory and severe symptomatic hypothyroidism after subtotal thyroidectomy in spite of high dose oral levothyroxine supplementation. By stepwise increasing oral levothyroxine dosage up to 2200 micrograms plus 80 micrograms of thyronine, no sufficient substitution could be achieved. After suspicion of enteral malabsorption due to a pathological D-Xylose-test, subcutaneous levothyroxine supplementation was started. Finally, a sustained euthyroid state could be achieved. - Conclusions: For selected patients who do not respond to oral treatment subcutaneous application of levothyroxine can be a suitable and effective therapy.